i think you got the right answer but what do you mean by this?
My first problem is, from the example equations, how can it be re-arranged and make 11?!
I need some real help with this please guys, ok so here's the example given to me from tutor:
Example 2x + y = 1, x + 3y = -7
Method 1 - add/subtract
2x + y = 1
x - 3y = 11
You can add or subtract. Adding will enable you to focus on x, subtracting will focus on y.
Perhaps the easiest is to add. BUT first of all you must scale the first expression by 3 to enable the y’s to match, giving the zero count for y, you require.
So 6x + 3y = 3 (Note each part has been x 3)
x - 3y = 11
Adding 7x = 14 (Note the zero count for y - this is what you x = 2 want to happen)
Substituting back into one of the previous expressions -
2(2) + y = 1, 4 + y = 1, y = -3
ANSWER x = 2, y = -3
My first problem is, from the example equations, how can it be re-arranged and make 11?!
I'm confused with this topic, thanks
ADY
2x + y = 1
x - 3y = 11
i call it elimination method
you can do that like this way. subtract the first from the second and get x.
now you have x
then use substitution method: you can use either 1st or second equation
substitute y to get x
now you have the value of both variables then substitute to check:
B.
A.
Note:11 is just the answer on the equation you are solving but there is no value of x and y so you need to find their values.